State Policies and Coffee: Indonesia–Brazil’s Journey from Colonialism for Global Markets - Khairizah; Sudiarto, Tatok Djoko (Yayasan Gema Bina Nusantara, 2025)
This study examines the role of the state in shaping the coffee industries of Indonesia and Brazil within the global market during the 20th century. The objective is to analyze how state intervention influenced the competitiveness of both countries’ coffee sectors. Using a qualitative and deductive approach grounded in international political economy and the concept of comparative advantage, the research finds that Brazil’s structured state-led interventions through infrastructure development, labor management, and export-oriented policies enabled it to dominate the global coffee industry. In contrast, Indonesia faced persistent challenges in modernization, distribution, and post-harvest management, limiting its competitiveness. The findings highlight the importance of consistent and proactive state policies in building competitive advantage for national commodities.